2017
DOI: 10.1016/j.physleta.2017.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Experimental realization of nondestructive discrimination of Bell states using a five-qubit quantum computer

Abstract: A scheme for distributed quantum measurement that allows nondestructive or indirect Bell measurement was proposed by Gupta et al., (Int. J. Quant. Infor. 5 (2007) 627) and subsequently realized experimentally using an NMR-based three-qubit quantum computer by Samal et al., (J. Phys. B, 43 (2010) 095508). In the present work, a similar experiment is performed using the five-qubit super-conductivity-based quantum computer, which has been recently placed in cloud by IBM Corporation. The experiment confirmed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…In fact, in Ref. [1] and other recent works using IBM quantum computers it is clearly observed that the state fidelity reduces considerably with the increase in the gate count. Further, because of this fact, each IBM quantum computer imposes a bound on the maximum number of gates that can be used in a single experiment.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In fact, in Ref. [1] and other recent works using IBM quantum computers it is clearly observed that the state fidelity reduces considerably with the increase in the gate count. Further, because of this fact, each IBM quantum computer imposes a bound on the maximum number of gates that can be used in a single experiment.…”
Section: Introductionmentioning
confidence: 89%
“…Again, six CNOTs can be realized directly and six can be realized by interchanging the target and control (as explained above.) For the following CNOTs (denoted as a pair of qubits, where the first qubit is the control and the second is the target) {(0, 4), (1,4), (3, 0), (3, 1), (4, 0), (4, 1)} we may exchange the control with qubit 2 at a cost of 10 additional gates using the swap gate approach, or with 9 additional gates using the template approach. Both methods are illustrated with an example below.…”
Section: A Qx2 Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, IBM has developed different types of prototypes of quantum processors and they are available by a free web based interface called IBM Quantum Experience (IBM QE). Researchers have taken a proper advantage of it by demonstrating and running a variety of quantum computing experiments, e.g., [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. Here, we use IBM's 5-qubit quantum processor, 'ibmqx4' to design the quantum circuit and perform the experiment by simulating it.…”
Section: Introductionmentioning
confidence: 99%
“…It is world's first commercial quantum computing service provided by IBM, and permits a user to run quantum algorithms via the IBM cloud and implement quantum circuits. Using this web interface researchers have run a variety of quantum computing experiments and demonstrations, e.g., [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%